2020
DOI: 10.2106/jbjs.cc.20.00226
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Acute Periprosthetic Knee Infection with Concurrent Presumed COVID-19

Abstract: Case: We report the case of a 64-year-old man who presented with a late onset of acute periprosthetic joint infection after total knee arthroplasty and a positive severe acute respiratory syndrome coronavirus 2 polymerase chain reaction test. We describe our perioperative protocol and challenges for ensuring the safety of healthcare providers while operating on a coronavirus disease 2019 (COVID-19)-positive patient. Conclusions: Given the incredible spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 47 studies included in the analysis, only 20 studies [ 16 , [18] , [19] , [20] , 24 , 25 , 29 , 32 , 39 , 42 , 45 , 46 , 50 , 53 , [55] , [56] , [57] , [58] , [59] , 61 ] reported the information of medical staff infection which identified that a total of 38 medical staff were infected, and medical staff who used biosafety level 3 (BSL-3) protective equipment during the perioperative period did not get infected.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were excluded if they reported tracheostomy outcomes only; did not involve a surgical intervention; the diagnosis of COVID-19 was based on symptoms or X-ray findings only; did not 16 Paris Urology All Yes Di Martino 17 Spain Gen Surg All Yes Alvarez Gallego 18 Spain Gen Surg All Yes Kayani 19 UK Ortho Emergency Yes Egol 20 USA Ortho Emergency Yes Cai 21 China Gen Surg Emergency Yes Javanmard-Emamghissi 22 UK Gen Surg Emergency Yes Barkhordari 23 Iran Cardiac Emergency Yes Sobti 24 UK Trauma/Orthopaedics Emergency Yes COVIDSurg Collaborative 8 Global All All No Dai 25 China Cancer Elective No Lei 26 China All Elective No Shrikhande 27 India Cancers Elective No Aminian 28 Iran Gen Surg Elective No Zhong 29 China Ortho/Gynae Emergency No Munoz Vives 30 Spain Ortho Emergency No Bellosta 31 Italy Vascular Emergency No Chen 32 China Caesarean Section Emergency No Senent-Boza 33 Spain All Emergency No Barret 34 Spain Burns Emergency No Hussain 35 London Cardiac Emergency No Li 36 China Thoracic Not stated No Case reports Gou, SM 37 China Pancreas Emergency Garcia-Portabella 38 Spain Ortho Emergency Davis-Sandfoss 39 USA Breast Cancer Elective Han 40 China Thoracic Emergency Lepre 41 Italy General Surgery Emergency Lyra 42 Portugal Obstetrics Elective Powezka 43 UK Vascular Emergency Qin 44 China Liver Transplant Emergency Rinaldi 45 Italy Vascular Emergency Stevenson 46 UK Ortho cancers Elective Sunkin 47 USA Orthopaedics Emergency Wen 48 China Neurosurgery Emergency Xuan 49 China Lung Transplant Emergency report on surgical outcomes; were incidence only studies, practice guidelines, consensus stateme...…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…One clinical case was found by authors as a result of the literature search on the topic in the PubMed and MEDLINE databases ( 16 ). This clinical case describes a patient with comorbid background with COVID-19 infection and PJI, and its management in the operating room.…”
Section: Discussionmentioning
confidence: 99%